Sustaining health in professional ballet: Insights into autonomy, shared expertise and open communication - Benoit-Piau, J.; Verhagen, E.; Morin, M.; Bolling, C. (Journal of Dance Medicine & Science, 2026)
Objectives: To explore the perceptions of dancers and the supporting staff regarding the management of dancers` health in a professional ballet company.